Religious Challenges and Guidance for Dayak Muslim Converts in the Indonesia–Malaysia Border Region - Masri, Moch Riza Fahmi; Sri Hidayati; Prasojo, Zaenuddin Hudi; Abdillah, Zulkifli; Zarbaliyev, Habib (Jurnal Theologia, 2025)
Religious conversion in border areas often triggers complex identity negotiations and social tension, particularly for indigenous communities like the Dayak people. In Jagoi Village, located at the Indonesia–Malaysia border, many Dayak individuals who convert to Islam face cultural, social, and spiritual challenges due to their minority status and the persistence of traditional customs. This study aims to identify the religious issues encountered by Dayak Muslim converts and evaluate the strategies of religious guidance based on religious moderation. Using a qualitative case study approach, data were collected through in-depth interviews, focus group discussions, and field observations involving religious counselors and local converts. The findings reveal four major problems: limited Islamic knowledge, minimal religious mentoring, poor access to digital Islamic resources, and a lack of understanding of religious moderation. This research contributes to the discourse on minority religious identity and offers policy recommendations for inclusive, culturally sensitive religious mentoring. It also supports the design of empowerment models for Muslim converts in border areas, which can serve as a reference for interreligious engagement and social integration efforts in Southeast Asia's plural societies.